Water Quality Assessment of Bagek Kembar Mangrove Ecosystem Using Phytoplankton as A Bioindicators - Yoszi Setiawan; Lalu Japa; Prapti Sedijani (Jurnal Biologi Tropis, 2026)
Mangrove ecosystems are highly dependent on surrounding water quality, which can be effectively assessed using biological indicators such as phytoplankton communities. This study aimed to analyze the water quality of the Bagek Kembar Mangrove Essential Ecosystem, West Lombok, based on phytoplankton community. The research employed a descriptive exploratory design with purposive sampling at three mangrove ecosystem types: pond area, rehabilitated mangrove, and natural mangrove. Phytoplankton samples were collected using a plankton net and analyzed for abundance, species diversity, evenness, and dominance. Physical and chemical parameters including temperature, pH, and salinity were also  study fully identified 67 species of phytoplankton with a total abundance of 2,542.5 ind/L. Merismopedia elegans was a dominant species, particularly in the pond area. Diversity indices ranged from low to moderate, evenness valuew indicated relatively stable communities, and dominance indexs showed no species dominance. These results indicated that the waters of the Bagek Kembar mangrove ecosystem are generally in good condition with mild ecological pressure influenced by anthropogenic activities. This study provides baseline ecological data to support sustainable management and conservation strategies for mangrove essential ecosystems of Bagek kembar, West Lombok.